Local Wisdom Tradisi Bodo Contong sebagai Guyub Rukun Masyarakat Desa Rahtawu - Linda Nurul Amaliyah; Faikhotur Rohmah; Muhammad Aziza; Yusuf Falaq (ARIMA : Jurnal Sosial Dan Humaniora, 2024)
Abstract There are many types of culture and traditions that develop on the island of Java, such as the one in Rahtawu Village, namely the Bodo Contong tradition. The Bodo Contong tradition is an activity carried out on the 15th of Nishfu Sya'ban in the Javanese calendar. This article aims to find out the local wisdom of the Bodo Contong tradition in Rahtawu Village, how values are actualized in society when implementing the Bodo Contong tradition. This research uses a qualitative descriptive approach with interview and documentation methods carried out on the Rahtawu village community. The results show that in the Bodo Contong tradition there is an actualization of the harmony of Rahtawu Village residents which is actualized through several local wisdom values such as religious values, philosophical values and social values. Key words: actualization; get along in harmony; Bodo Contong tradition. Abstrak Budaya dan tradisi yang berkembang di pulau jawa sangat banyak jenisnya, seperti yang ada di Desa Rahtawu yaitu tradisi Bodo Contong. Tradisi Bodo Contong merupakan kegiatan yang dilaksanakan tanggal 15 nishfu sya’ban dalam hitungan kalender Jawa. Artikel ini bertujuan untuk mengetahui kearifan lokal tradisi Bodo Contong di Desa Rahtawu, bagaimana aktualisasi nilai dalam masyarakat saat pelaksanaan tradisi Bodo Contong. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan metode wawancara dan dokumentasi yang dilakukan pada masyarakat desa Rahtawu. Hasil menunjukkan bahwa dalam tradisi Bodo Contong terdapat aktualisasi guyub rukun warga Desa Rahtawu yang diaktualisasikan melalui beberapa nilai kearifan lokal seperti, nilai religius, nilai filosofis, dan nilai sosial.